Electrocatalytic detection of herbicide, amitrole on the platform modified with polyaniline cobalt phthalocyaninato doped with cobalt oxide nanoparticles. - Mafuwe, Peter T. (Midlands State University, 2017)
An electrochemical sensor based on polyaniline cobalt phtahlocyanito doped with cobalt oxide nanoparticles was developed for the electrocatalytic oxidation of amitrole.FTIR, Electrochemical impedance spectroscopy (EIS) and Bode plots were used in the characterization of the synthesized modifiers CoTCPc, PANI, Co2O3NPs and to ascertain the chemical linkage between CoTCPc and PANI while cyclic voltammetry, linear sweep, chronoamperometry and differential pulse voltammetry were used to assess the electrocatalytic efficiency of the linked product towards oxidation of amitrole. The surface area of the modified electrode was 0.40 cm2 and the surface coverage was 7.60× 10-13 molcm2.The catalytic rate constant was of 6.26×105M-1s-1and the apparent electron transfer rate constant was 8.84 × 10-3cm s-1.The adsorptionequilibrium constant was 3.8× 103 M-1and Gibbs free energy was -20.42kJ. The limit of detection was 6.612 × 10-8M and the limit of quantification was 2× 10-7 M. Interference studies were done and the electrode displayed the ability to detect both amitrole and nitrates. The electrode displayed good reproducibility with lower oxidation potential at 0.8 V and high sensitivity towards amitrole.